SISTEM INFORMASI MEDIA LATIHAN PERSIAPAN UN MATEMATIKA SMP NEGERI 2 MERANGIN - Rahimullaily Rahimullaily; Heru Saputra; Wahyu Johandri (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2018)
In doing the exercise & try out SMP Negeri 2 Merangin not using computerized system. Such a system has some constraints that students can not learn to process without teachers, students can not know the results of the exercise on the same day, the teacher takes a long time in doing the correction of student exercises. Therefore, the design of this system aims to maximize the preparation process of Ujian Nasional Mathematics students in SMP Negeri 2 Merangin. The methodology used in this research is field research, library research, laboratory research and SDLC concept (system development life cycle). The results achieved by the design of media information system of the preparation work of Ujian Nasional Mathematics SMP Negeri 2 Merangin, which is in the form of a computerized database information system design that can facilitate students and teachers SMP Negeri 2 Merangin in doing the exercises and correction.Keywords: try out, ujian nasional, system development life cycle